Nilai Kehidupan Dalam Penciptaan Karya “Darmaning Satriya Pinandhita” - Wijaya, Indra Danar; Asmoro, Purbo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
Anoman or Hanuman is a popular figure from the great epic Ramayana who is known by many groups. He took the form of a white monkey with extraordinary powers that were once said to be able to burn down the Alengka Kingdom and lift a mountain. Not only in the Ramayana, the character Anoman also appears in the Mahabarata stories. As told in the Mahabarata, Anoman met his apprentice brother, Raden Werkudara or Bima, who was also a student of the wind god, Batara Bayu. In the Javanese Pedalangan story, Anoman’s story even continues until the Middle Ages, namely the era of the Pandava descendants in the Kingdom of Kediri. It is said that Anoman, who was elderly by the name of Resi Mayangkara, tried to reconcile the Pandawa descendants until he met his death. The work methods used are orientation, exploration and observation. The data collection technique used is literature study. The concept used to compile this work is the concept of solid packaging. The result of this work is a work entitled Darmaning Satria Pinandhita.